Deskripsi Pengembangan UMKM Berbasis Tempe Melalui Peran Aparatur Gampong di Desa Purwodadi Kecamatan Kuala Pesisir Kabupaten Nagan Raya - Siti Maghfirah; Ivon Jalil (Universitas Teuku Umar, 2023)
Tempe-based Micro, Small and Medium Enterprises (MSMEs) are one of the potentials in Purwodadi Village. The purpose of this study is to see the role of the village apparatus in the development, empowerment and development of MSMEs in Purwodadi village. The results of observations and interviews show that the problems generally lie in capital, facilities, rising raw material prices, the absence of SIUP and SITU, the absence of tempe-based innovative product development, and the low knowledge and ability of MSME actors regarding marketing strategies. The method applied is using the FGD (Focus Group Discussion) approach through the PALS (Participatory action learning System) method, Preliminary Survey, counseling or lectures. So that the implementation of the program was carried out well, such as socialization activities, FGD, Bimtek, SIUP and SITU management assistance, Phase I and Phase II Empowerment. In this case Purposive Sampling is the method used to determine the source. The conclusion of this study is that tempe-based business actors have obtained a form of legality of their business, naming a business label (Brand), able to process tempe innovation products such as: tempe nuggets, tempe meatballs, tempe broth and tempe chips. On the other hand, MSME groups have also been formed. creative under the supervision of BumDes.